Decoding water quality across urban and rural dental clinics: insights from an observational study - Vatanparast, Bahar; Florez Salamanca, Elkin; Singh, Amrinderbir; Siqueira, Michelle F. (Frontiers in Oral Health, 2025)
IntroductionAdherence to drinking water standards in dental treatments is a critical measure for preventing nosocomial infections. This study aimed to evaluate water quality from dental unit waterlines (DUWLs) and clinic taps over eight months in urban and rural dental clinics across Saskatchewan, Canada.MethodsStaff from one urban dental clinic and three rural clinics underwent refresher training on maintaining DUWLs. Training included protocols for flushing lines, using disinfecting tablets, shocking lines with sodium hypochlorite, and proper sample collection. Water samples were aseptically collected from DUWLs and clinic taps using Sigma-Aldrich® waterline test kits and analyzed at a quality assurance laboratory for bacterial contamination. Samples were incubated for seven days and categorized based on bacterial colony counts. Failed DUWL tests (CFU/ml > 500) were repeated after shocking procedures. Statistical analysis included frequency calculations, cross-tabulations, and Chi-square tests, with significance set at α = 0.05.ResultsA total of 399 samples were analyzed over eight months. Among DUWL samples, 14.9% from the urban clinic and 36.4% from rural clinics failed quality standards. Tap water from the urban clinic showed no failures, whereas 46.9% of rural tap water samples failed. Urban clinics had faster retesting, with 71% completing retests within one week, compared to 28% in rural clinics. Rural retest failure rates were 33.5% compared to 10% at urban clinics.DiscussionDisparities in water quality between urban and rural dental clinics in Saskatchewan were evident, with rural clinics exhibiting higher contamination rates and slower remediation actions. These findings underscore the urgent need for enhanced infection control measures, including targeted staff training, implementation of robust waterline maintenance protocols, prompt retesting practices, and consideration of alternative tap water sources in rural settings. Addressing these challenges is essential to ensuring safe and equitable dental care while reducing the risks associated with contaminated water.